Study on the Characteristics of Top-Coal Caving and Optimization of Recovery Ratio in Steeply Inclined Residual High Sectional Coal Pillar. (1st September 2020) - Yang, Wenhua; Lai, Xingping; Shan, Pengfei; Cui, Feng; Yang, Yiran
Abstract : This paper is aimed at solving the technical problems such as low recovery ratio and frequent disasters in steeply inclined and extrathick coal seams at residual high sectional coal pillar. It takes the Wudong Coal Mine as an engineering background, a typical mine of steeply inclined and extrathick coal seams; the structural features of the top-coal caving at the steeply inclined residual high sectional coal pillar were analyzed using methods such as field monitoring and numerical simulation; a mechanical model of the top-coal arch structure was constructed, and the calculation method of top-coal caving height and related influencing factors was obtained. The results showed that the top-coal caving in the steeply inclined residual high sectional coal pillar was characterized as arch. Due to the existence of arch structure, the smooth caving of the top coal was hindered, resulting in a low top-coal recovery ratio, low support pressure at the working face, and differences detected by borehole television on the distribution of the top-coal cracks. With the advancement of the working face, the top-coal arch structure was in the process of dynamic evolution, as the old arch balance system was continuously replaced by the new arch balance system, and it continuously moved towards the upper top coal. The top-coal caving height was affected by factors such as length of the working face, bulk density of overlying coal rock, and cohesion of the top coal. The top-coal caving height increased with the length of the working face and the bulk density of the overlying coal rock mass but was inversely proportional to the cohesion of the top coal. Under the current mining conditions, the top-coal caving height was 39.8 m, which was much lower than the residual high sectional coal pillar height (71 m); the top coal cannot collapse completely. Based on the characteristics of the top-coal caving structure, the technology of sublevel advanced presplitting blasting was adopted to weaken the top coal in engineering practice, so that the top-coal caving structure moved up naturally. The daily coal production in the working face has increased by an average of 2419.6 tons, which has significantly improved the top-coal recovery ratio and production efficiency. The result provided a theoretical basis and application reference for similar residual high sectional coal pillar recovery.